2004
DOI: 10.1042/bj20031326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycosylphosphatidylinositol (GPI)-phospholipase D overexpression on GPI metabolism

Abstract: GPI-PLD [glycosylphosphatidylinositol (GPI)-specific phospholipase D (PLD)] is a secreted mammalian enzyme that specifically cleaves GPI-anchored proteins. In addition, the enzyme has been shown to cleave GPI anchor intermediates in cell lysates. The biosynthesis of the GPI anchor is well characterized; however, the mechanisms by which the levels of GPI anchor intermediates are regulated are still unknown. To investigate whether GPI-PLD plays a role in this regulation, we isolated stable HeLa cells overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 41 publications
2
25
0
1
Order By: Relevance
“…A related protein found in this study is GPI-PLD which cleaves the GPI anchor sequence attached to many cell surface proteins including receptors. 57 GPI-PLD was downregulated in the estrogen and combined treatment groups, which is consistent with reports that this protein was decreased during inflammation 58 and which can be related to tumor growth.…”
Section: The Nude Mouse Xenograft As a Model For Breast Cancersupporting
confidence: 92%
“…A related protein found in this study is GPI-PLD which cleaves the GPI anchor sequence attached to many cell surface proteins including receptors. 57 GPI-PLD was downregulated in the estrogen and combined treatment groups, which is consistent with reports that this protein was decreased during inflammation 58 and which can be related to tumor growth.…”
Section: The Nude Mouse Xenograft As a Model For Breast Cancersupporting
confidence: 92%
“…Initial reports indicated that GPI-PLD was active against GPI-anchored proteins only in the presence of detergent, and was not able to cleave the anchors of proteins in a native membrane context [218]. Overexpression experiments indicated that it is active in endoplasmic reticulum during GPI synthesis, but also in lipid rafts [219]. Lipid fluidity and packing are the most important modulators of bacterial phospholipase ability to cleave GPI anchors [220] and modulation of membrane lipids were reported to affect GPI-PLD activity in vitro [221], so it is quite possible that mammalian GPI-PLD also requires particular membrane composition for activity.…”
Section: Two Types Of Gpi-specific Phospholipases Gpi-phospholipase mentioning
confidence: 99%
“…TNAP is a GPI-anchored ecto-enzyme 22 , and in the secretory pathway GPI-PLD cleaves the GPI anchor from TNAP 3741 , and TNAP becomes a secreted, soluble enzyme. GPI-PLD activity is inhibited by protein kinase A (PKA)-mediated phosphorylation of threonine 286 42 .…”
Section: Discussionmentioning
confidence: 99%